Persepsi perusahaan asing dan perusahaan dalam negeri yang tidak go public terhadap kebutuhan jasa akuntan publik - Januar Eko Prasetyo (Jurnal Akuntansi dan Auditing Indonesia, 2001)
This research aims at finding out the differences perceptions between multinational and domestic companies toward the needs of public accounting services, and knowing the differences perception among kinds of multinational and domestic companies toward the needs of public accounting services. Thus, it can be seen the perception levels the needs of public accounting services which is reflected by the perception toward the problems needs of public accounting services. The measurement of perception includes the general needs of public accounting, management consultation, finance report, auditing and taxation services.